2005
DOI: 10.1248/bpb.28.2117
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase Genotype and Phenotype Status in Japanese Patients with Systemic Lupus Erythematosus

Abstract: Thiopurine methyltransferase (TPMT) catalyses the Smethylation in azathioprine (AZA), thioguanine and 6-mercaptopurine (6-MP).1,2) The low TPMT activity in erythrocytes has been associated with an increased risk of severe and potentially fatal hematopoietic toxicity caused by the accumulation of the cytotoxic metabolites of thiopurine drugs. [3][4][5][6]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Okada et al [193] investigated genotype and phenotype status in 68 Japanese patients with SLE and in 174 healthy volunteers. Although most patients tolerated AZA well, the drug was withdrawn in 3 cases because of leukopenia (two *1/*1 and one *1/*3C).…”
Section: Studies In Patients With Rheumatologic Disordersmentioning
confidence: 99%
“…Okada et al [193] investigated genotype and phenotype status in 68 Japanese patients with SLE and in 174 healthy volunteers. Although most patients tolerated AZA well, the drug was withdrawn in 3 cases because of leukopenia (two *1/*1 and one *1/*3C).…”
Section: Studies In Patients With Rheumatologic Disordersmentioning
confidence: 99%
“…Clinical trials of AZA treatment for SLE have shown that the withdrawal rate was 0-5% during the study period of 42-72 months (18, 19). Furthermore, observational studies in SLE patients have shown that only 4.5-6.4% of patients discontinued AZA treatment, which is representative of what is observed in daily clinical practice (15, 20, 21). Considering these low AZA treatment discontinuation rates in previous AAV and SLE studies, we conclude that the high discontinuation rate of AZA in the present study was not caused by disease specificity but by other factors.…”
Section: Discussionmentioning
confidence: 76%
“…Why AZA is used less frequently for Japanese AAV patients than Western ones remains unclear. There is no evidence of AZA tolerability among Japanese AAV patients, although some studies have shown that AZA withdrawal was 4.4% among Japanese systemic lupus erythematosus (SLE) patients (15) and 19% among Japanese IBD patients (9). Furthermore, the risk factors for AZA toxicity in AAV patients have never been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, TPMT * 3C variant genotypes were found in five of 49 patients with AIH (10%). In previous Japanese studies, TPMT * 3C variant genotypes were detected in eight of 323 (2.5%) healthy individuals, four of 174 (2.3%) healthy volunteers, and 1 of 151 (0.7%) healthy volunteers (8, 21, 22). We speculated that the prevalence of the TPMT * 3C variant genotype is similar in Japanese patients with HCV and healthy Japanese subjects.…”
Section: Discussionmentioning
confidence: 86%
“…Our data are comparable to the high prevalence of TPMT polymorphism in the United Kingdom. It was reported that TPMT * 3C variants were found in seven of 192 (3.6%) patients with rheumatic diseases and four of 68 (5.9%) patients with systemic lupus erythematosus (8, 21). The frequency of TPMT * 3C variants in the AIH group was slightly but not significantly higher than that in other autoimmune diseases in our study.…”
Section: Discussionmentioning
confidence: 99%